Association Between Blood Pressure Variation During Dialysis and Cardio‐Cerebrovascular Events - Zhenliang Fan; Rujia Ye; Qiaorui Yang; Mengfan Yang; Riping Yin; Dongxue Zhao; Junfen Fan; Hongzhen Ma; Yiwei Shen; Hong Xia; Wenze Jiang; Keda Lu (The Journal of Clinical Hypertension, 2025)
ABSTRACT In hemodialysis patients, blood pressure variability (BPV) is associated with cardiovascular events and all‐cause mortality. However, previous research has predominantly concentrated on the predialysis BPV. In contrast, intradialytic BPV, reflecting the cardiovascular regulatory function during the process of rapid clearance of volume overload, holds greater relevance to the prognosis of patients. In this study, a latent category trajectory model was used to identify the patterns of intradialytic BPV and analyze the association between intradialytic BPV and the cardio‐cerebrovascular events and other clinical outcomes. We found the variation of intradialytic systolic blood pressure (SBP) was associated with the risk of cardio‐cerebrovascular events in hemodialysis patients. Patients in “SBP Class 4” and “SBP Class 3” subgroups were associated with the occurrence of cardio‐cerebrovascular events and the number of cardio‐cerebrovascular event hospitalizations during the follow‐up period. This indicates that the variation pattern of intradialytic SBP results from the comprehensive action of various BP regulatory mechanisms in the body, which can reflect the level of cardiovascular regulatory function in hemodialysis patients and serve as a predictor of recent adverse cardio‐cerebrovascular events.